Avaliação da potabilidade da água na subsuperfície de cemitérios da cidade Capanema (Pará, Brasil) - OLIVEIRA, Fabiana de Sousa (2023)
Cemeteries have a great capacity to harm the earth's surface, the surface and underground waters, and the ecosystem around them because of the decomposition process the bodies undergo. The present work evaluated the potability of water in places close to the São José and Cemitério Parque Municipal São Francisco de Assis cemeteries, both in the municipality of Capanema, northeast of the state of Pará (Brazil). The methodology included the application of a socio-environmental questionnaire, in addition to a microbiological and physical analysis of water samples from artesian wells collected in homes close to the cemeteries. In the microbiological analyses of the water samples, 75% of the samples from the cemeteries presented total coliform bacteria and the Escherichia Coli, which is the primarily responsible for most of the urinary, kidney and other infections. In the physical test, only one sample exceeded the Maximum Permissible Value for turbidity established by the current legislation. In the socio-environmental questionnaire, approximately 93.75% of the interviewees stated that they have never questioned themselves about the potability of water, 68.75% never noticed changes in the water consumed. Among the main symptoms of diseases, abdominal pain (31.25 %) is the most frequent. Therefore, the contamination of groundwater near the two cemeteries in the city of Capanema is a serious issue, as people often show symptoms of diseases that have this contamination as probable causes.